2018
DOI: 10.1186/s13075-018-1577-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selexipag and its active metabolite in contrasting the profibrotic myofibroblast activity in cultured scleroderma skin fibroblasts

Abstract: BackgroundMyofibroblasts contribute to fibrosis through the overproduction of extracellular matrix (ECM) proteins, primarily type I collagen (COL-1) and fibronectin (FN), a process which is mediated in systemic sclerosis (SSc) by the activation of fibrogenic intracellular signaling transduction molecules, including extracellular signal-regulated kinases 1 and 2 (Erk1/2) and protein kinase B (Akt). Selexipag is a prostacyclin receptor agonist synthesized for the treatment of pulmonary arterial hypertension. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Since myofibroblasts have been considered to be a pivotal contributor to the progression of fibrosis in SSc, we aimed to investigate whether the LTB 4 -BLT1 axis has a direct influence on myofibroblast differentiation. In addition to the well-accepted evidence of fibroblast-myofibroblast transitions that take place in a variety of fibrotic processes, including SSc (24,25), recent novel findings have suggested that endothelial-mesenchymal transitions may also act as a mechanism for the generation of activated myofibroblasts in SSc (6). Results of the present study demonstrated that BLT1 was expressed in fibroblasts, including primary human dermal fibroblasts (HDFs), embryonic fibroblast cells (NIH/3T3 cell line), and human fetal lung fibroblast cells (MRC-5 cell line), as well as in human umbilical vein endothelial cells (HUVECs) at both the messenger RNA (mRNA) and protein levels (see Supplementary Figures 2A and B, available on the Arthritis & Rheumatology web site at http://onlin elibr ary.wiley.com/doi/10.1002/art.41119 2/ abstract).…”
Section: Ltb 4 -Blt1 Axis-dependent Induction Of Myofibroblast Differmentioning
confidence: 99%
“…Since myofibroblasts have been considered to be a pivotal contributor to the progression of fibrosis in SSc, we aimed to investigate whether the LTB 4 -BLT1 axis has a direct influence on myofibroblast differentiation. In addition to the well-accepted evidence of fibroblast-myofibroblast transitions that take place in a variety of fibrotic processes, including SSc (24,25), recent novel findings have suggested that endothelial-mesenchymal transitions may also act as a mechanism for the generation of activated myofibroblasts in SSc (6). Results of the present study demonstrated that BLT1 was expressed in fibroblasts, including primary human dermal fibroblasts (HDFs), embryonic fibroblast cells (NIH/3T3 cell line), and human fetal lung fibroblast cells (MRC-5 cell line), as well as in human umbilical vein endothelial cells (HUVECs) at both the messenger RNA (mRNA) and protein levels (see Supplementary Figures 2A and B, available on the Arthritis & Rheumatology web site at http://onlin elibr ary.wiley.com/doi/10.1002/art.41119 2/ abstract).…”
Section: Ltb 4 -Blt1 Axis-dependent Induction Of Myofibroblast Differmentioning
confidence: 99%
“…In the ‘non-inhibitor’ groups, the collagen-I and FN levels in the M group were insignificantly higher compared with the N group, whereas significant ECM deposition was observed in the S group. As important components of ECM, collagen-I and FN are often used to indicate the severity of fibrosis (33). In the non-inhibitor groups, ECM deposition did not change significantly in the M group but increased significantly in the S group.…”
Section: Discussionmentioning
confidence: 99%
“…Selexipag, an oral selective IP prostacyclin-receptor agonist, has demonstrated positive effects on pulmonary arterial hypertension (PAH) in both patients with and without connective tissue disease, 28,29 and may have direct activity on SSc patients' fibroblasts. 30 Recently, selexipag was tested in an RCT of 74 patients with SSc, and no significant differences were identified on Raynaud's phenomenon number or duration of attacks. At baseline, DUs were present in eight and three patients in the placebo and selexipag groups, respectively.…”
Section: Prostanoidsmentioning
confidence: 99%